Econometric Analysis of the Relationship between Renewable Energy Production, Traditional Energy Production and Unemployment: The Case of Azerbaijan - Huseynli, Bahman; Huseynli, Nigar (International Journal of Energy Economics and Policy, 2022)
The aim of this study is to determine the relationship between Azerbaijan`s traditional energy production, renewable energy production and unemployment rates. While performing the analysis, it was first tested whether the data were stationary or not. The data were stabilized by using the Augmented Dickey–Fuller test (ADF). After making the data stationary, the VAR model was established, and appropriate lag lengths were determined. The relationship between the data was analyzed by using the Granger Causality test at the end. Finally, the direction and strength of the relationship between the variables were tried to be determined by making correlation analysis between the variables. According to the results of the Granger analysis, a causal relationship was found between unemployment and renewable energy production, and between renewable energy production and traditional energy production based on 2005-2015 data in Azerbaijan.